2003
DOI: 10.1128/aac.47.10.3368-3370.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Megazol, a Trypanocidal Nitroimidazole, Is Associated with DNA Damage

Abstract: DNA damage associated with the trypanocidal activity of megazol [2-amino-5-(1-methyl-5-nitro-2-imidazolyl)-1,3,4-thiadiazole] was shown in experiments in which DNA repair-deficient RAD51؊/؊ Trypanosoma brucei mutants were found to be hypersensitive to the drug. Parasites resistant to megazol were selected and showed modest cross-resistance to other trypanocides, although neither drug efflux nor changes to intracellular thiols correlated with resistance.New drugs are urgently required for treatment of human Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 30 publications
(20 reference statements)
1
31
1
1
Order By: Relevance
“…Similar approaches with an in vitro model with megazol in T. brucei (11) and with Leishmania (17) have been reported. Nevertheless, in the Leishmania model BSO was barely effective (17).…”
Section: Discussionmentioning
confidence: 69%
“…Similar approaches with an in vitro model with megazol in T. brucei (11) and with Leishmania (17) have been reported. Nevertheless, in the Leishmania model BSO was barely effective (17).…”
Section: Discussionmentioning
confidence: 69%
“…The action of nifurtimox, however, is antagonized by NAC, whereas that of megazol is not. It therefore appears that megazol acts through reductive stress, whereas nifurtimox acts through oxidative stress (16,18). Compound 3a does not have any enhanced activity against the RAD51 knockout cells, which indicates that this compound may not exert its activity through reductive stress.…”
Section: Discussionmentioning
confidence: 92%
“…Using the RAD51 knockout line and NAC assay system, we have shown that the nitroimidazole-thiadazole megazol exerts its activity through reductive stress as RAD51 knockout parasites, which are deficient in DNA repair and hypersensitive to this drug (18). These cells are not hypersensitive to the nitrofuran nifurtimox.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations